The King of Capri - Winterson, Jeanette, 1959-; Ray, Jane (New York : Bloomsbury Children$1 (Bs Book,s, 2003)
The greedy and self-centered king of Capri has a reversal of fortune when the wind blows all of his precious things into the backyard of a kind and generous Naples washerwoman, Mrs. Jewel.
Keywords: Fairy tales; Kings, queens, rulers, etc. -- Fiction; Greed -- Fiction; Italy -- Fiction